A new species of Gonatodes (Squamata: Sphaerodactylidae) from the western versant of the Cordillera de Mérida, Venezuela - Schargel, Walter E.; Rivas, Gilson A.; García-Pérez, Juan E.; Rivero-Blanco, Carlos; Chippindale, Paul T.; Fujita, Matthew K. (Zootaxa, 2017)
Gonatodes rayito sp. nov. is described from the western versant of the Cordillera de Mérida, Venezuela. Like most species of Gonatodes the new species is sexually dichromatic and is one of only a few in the genus in which individuals have a conspicuous, pale middorsal stripe. The new species is similar to, and has been confused in the past with, G. petersi and G. vittatus. It differs from both species in several aspects of color pattern, and also from G. vittatus in size and scale counts. The validity of Gonatodes rayito sp. nov. is also strongly supported by a phylogenetic analysis using a fragment of the ornithine decarboxylase nuclear gene.